A Fast Algorithm for a Class of Generalized Fractional Programs - Gugat, Martin (Management Science, 1996)
In many decision problems, criteria occur that can be expressed as ratios. The corresponding optimization problems are nonconvex programs of fractional type. In this paper, an algorithm for the numerical solution of these problems is introduced that converges always at superlinear speed. Numerical examples are presented.